The Influence of Front Office Service Quality on Guest Satisfaction at Courtyard by Marriott Bali Nusa Dua Resort - Agripina, Kadek Samanta; Kalpikawati, Ida Ayu; Sabudi, I Nyoman Sukana (Journal of Hospitality Accommodation Management (JHAM), 2025)
Service quality plays a vital role in the hospitality industry as it directly influences guest satisfaction, customer loyalty, as well as the image and sustainability of a hotel. As the primary point of guest interaction, the front office is crucial in shaping first impressions and creating a pleasant and memorable stay experience. This study aims to examine the effect of front office employees’ service quality on guest satisfaction at Courtyard by Marriott Bali Nusa Dua Resort. A quantitative descriptive approach was employed, with data collected through questionnaires distributed to 120 hotel guests. Data analysis included validity and reliability testing, simple linear regression, and t-tests using SPSS version 26. Service quality was measured using the SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The findings reveal that the service quality of front office staff has a positive and significant impact on guest satisfaction. This suggests that responsive, courteous, and personalized service enhances guest comfort and overall stay experience. The study highlights the importance of continuous training and evaluation for front office employees to maintain consistent service quality and ensure that guest expectations are met.